TYPES OF DETERMINING THE PHYSICAL DEVELOPMENT OF MIDDLE-DISTANCE RUNNERS (International journal of artificial intelligence, 2025)
This article reveals the results of a comparative analysis with the data provided by leading scientists to determine the physical development of middle-distance runners and the effects of physical development, step length, frequency, and running speed.